Voltammetric Determination of Aflatoxin B1; Procedia Chemistry; Vol. 10 : Chemistry and Chemical Engineering in XXI century - Gavrilova M. A.; Slepchenko G. B. Galina Borisovna; Mikheeva E. V. Elena Valentinovna; Deryabina V. I. Valentina Ivanovna (2014, 2014)
Title screen